Pengaruh Kesan Kualitas Layanan, Harga, dan Kepuasan Mahasiswa PTS terhadap Minat Mereferensikan Kampusnya - Djati, S. Pantja; Darmawan, Didit (Jurnal Widya Manajemen & Akuntansi, 2004)
Organization have to take advantage of every opportunity in order to develop better relationships with customers, specially in competitive environments. The favorable impact of perceived service quality is generally explained by satisfaction and word of mouth behavior. This study will be focused on the effect of perceived service quality to customer satisfaction and intension to reference. Price variable would have the same role as perceived service quality variable. Universities offered those essensial things.